From Dust to Digital: Ten Years of the Endangered Archives Programme - Kominko, Maja (Open Book Publishers, 2015)
"Much of worldâ s documentary heritage rests in vulnerable, little-known and often inaccessible archives. Many of these archives preserve information that may cast new light on historical phenomena and lead to their reinterpretation. But such rich collections are often at risk of being lost before the history they capture is recorded. This volume celebrates the tenth anniversary of the Endangered Archives Programme at the British Library, established to document and publish online formerly inaccessible and neglected archives from across the globe. From Dust to Digital showcases the historical significance of the collections identified, catalogued and digitised through the Programme, bringing together articles on 19 of the 244 projects supported since its inception. These contributions demonstrate the range of materials documented â including rock inscriptions, manuscripts, archival records, newspapers, photographs and sound archives â and the wide geographical scope of the Programme. Many of the documents are published here for the first time, illustrating the potential these collections have to further our understanding of history."